China's Challenge to the West: Possibility and Reality. Issue 1 (2nd January 2017) - Jefferies, William
ABSTRACT: Leo Panitch and Sam Gindin's article "The Integration of China into Global Capitalism" argues that China will follow the pattern of post-war Japan to become a supplemental, junior partner in supporting US hegemony. They claim that due to the close trade and financial ties between the United States and China, there is no question of China challenging America's dominance of the global system (Panitch and Gindin 2013). This article will critically examine the premises of this claim, taking account of the post-war history of Japan; the measure of transition to market forms in China's economy; the role of trade; China's overall level of development; and the growth of the country's domestic corporations. The article focuses particularly on the level of China's domestic technology measured through Patents in Force (PiFs). It argues against Panitch and Gindin that China is poised to challenge Western dominance of the world economy.